Blood Relations: Collective Memory, Cultural Trauma, & the Prosecution & Execution of Timothy McVeigh - Madeira, Jody Lynee (2008)
In the aftermath of the Oklahoma City bombing, processes of reconstruction - remembering victims, caring for family members and survivors, and punishing the perpetrators - began even as debris from the Murrah Federal Building was being cleared. Based on conclusions obtained from intensive interviews with 27 victims' family members and survivors, this article explores how memory of the bombing as a culturally traumatic event was constructed through participation in groups formed after the bombing and participation in the legal proceedings against perpetrators Timothy McVeigh and Terry Nichols. These acts cultivated the formation of various relationships - between family members and survivors as well as between these victimized populations and the perpetrators - that both helped and hindered individual and communal reconstructions of meaning. This article will first address the efficacy of a collective memory and cultural trauma perspective for analyzing two collective processes of sense-making - group membership and legal proceedings - in the aftermath of the Oklahoma City bombing. It will then briefly describe the mental context in which family members and survivors joined groups in the wake of the bombing, and the functions those groups played in trauma recovery, after which it will summarize the impact of group membership on punishment expectations. Next, it will discuss the involuntary relationship that formed between McVeigh and family members and survivors predicated on the social and media representations of McVeigh; due to this relationship, McVeigh was felt to be a constant presence in victims' lives until his 2001 execution. Finally, this article will examine family members' and survivors' perceptions of communicative interchange with McVeigh in the venues of the trial and execution. The implications of this case study illustrate in what ways concepts such as victimhood and justice are continually being expanded, with the implication that law is not only a social institution that mediates cultural trauma and cultivates collective memory, but also is manifestly conscious of these roles